PENGELOLAAN LIMBAH CAIR JASA PENCUCIAN KENDARAAN DENGAN METODE ELEKTROKOAGULASI - Tuhu Agung Rachmanto; Elcyber Alqadri Andili (EnviroUS, 2021)
Vehicle washing service generally does not have a waste treatment system to handle liquid waste generated from the washing process. There are several methods of waste treatment that are efficient. One of them is the electrocoagulation process which is a water treatment technology using an electrochemical process where the anode will release active coagulants in the form of ions into the wastewater solution to form flocs that are able to bind contaminants and particles in the waste. This study aims to reduce the concentration of TSS in washing wastewater. motorized vehicles and to find out changes in pH naturally with independent variables, namely changes in time, changes in voltage and types of electrodes using the electrocoagulation method. The research was carried out in batches using Aluminum (AI) and Iron (Fe) plates as electrodes with time variations of 30, 60, 90, 120 minutes and voltage variations of 3, 6, 9, 12 Volts. The parameters measured were TSS and pH. the results of the study obtained optimal results for the efficiency of TSS removal with aluminum (AI) electrodes of 93.15% from 253 mg/l to 57.25 mg/l with a voltage of 12 volts with a sampling time of 120 minutes. Keywords: Vehicle Washing Waste, Electrocoagulation, TSS